Onymic space of Ukrainian comparative paramias (based on the material from the collection of Matviy Nomys “Ukrainian sayings, proverbs, and the like”) - Бондаренко, Максим Олегович (Київський національний університет імені Тараса Шевченка, 2023)
Background. In today’s dynamic world, Ukrainians, like other peoples, are trying to preserve their national identity. Studying the peculiarities of the linguistic world of our ancestors becomes a primary task in modern linguistics, because language is a kind of mediator that ensures continuous communication between different generations. For many of us, it is important to feel the persistence of language and cultural traditions. The paremic subsystem of the Ukrainian language is the most interesting and the most eloquent. The study of paremias not only makes it possible to delve into the depths of the ages and trace the purely lexical or grammatical features of the language at a certain synchronous section, but also to try to reproduce important fragments of the linguistic picture of the world of our ancestors, which will help to understand their way of thinking. The purpose of this study is to find out the peculiarities of the organization of the onymic space of comparative paremias, attested in the collection of M. Nomys “Ukrainian proverbs, sayings, and the like” (1864), to determine the role of precedent onyms, which are important components of comparative proverbs and sayings, in the linguistic picture of the world of Ukrainians of the 19th century. Methods. The comparative and qualitative methods were applied. Results. During the study, the structure of the onymic space was characterized, its components – onymic fields (anthroponymic, toponymic, as well as ethnonymic) were distinguished and analyzed. It was found that the anthroponymic field is quite informative and bright, which most often includes units with such anthroponyms and their derivatives: Настя, Сидір, Хведько, Семен, etc. In addition, comparative paremias with precedent onyms (Гоне, як вітрів батько; Побілів, як Пилат) are considered and characterized. The onymic components of these units have a wide cultural and historical context, and are also powerful linguistic and ethnocultural codes of the Ukrainian people. The field of toponyms is valuable for the study of socio-historical realities. Proverbs and sayings often include the following toponyms and their derivatives: Очаків, Переяслав, Поділля, Полісся, etc. It is not surprising that the ethnonymic field is the largest. The collection of M. Nomys contains proverbs and sayings, which include the following ethnonyms: жид, циган, москаль, русин, швед, татарин, etc. The conducted study of the onymic space of Ukrainian comparative paremias made it possible to characterize the system of views and value orientations of our ancestors, to reconstruct the fragments of the linguistic and conceptual pictures of the world of Ukrainians of the 19th century, which are partly lost today.

Проаналізовано засвідчені в збірці Матвія Номиса “Українські приказки, прислів’я і таке інше” (1864) компаративні паремії з онімним компонентом, що формують цілісний онімний простір. Схарактеризовано його структурну організацію, виокремлено та розглянуто онімні поля – антропонімне, топонімне, а також етнонімне (яке деякі дослідники зараховують до онімних). З’ясовано специфіку прецедентних онімів, які є потужними лінгвокультуремами. На матеріалі порівняльних конструкцій зі сполучником простежено вербалізацію особливостей концептуальної картини світу українців XIX ст., їхнього світосприйняття і способу мислення.
Онімний простір українських компаративних паремій (на матеріалі збірки Матвія Номиса “Українські приказки, прислів’я і таке інше”)
Keywords: компаративні паремії; онімний простір; онімне поле; антропонім; топонім; етнонім; прецедентний онім; comparative paremias; onymic space; onymic field; anthroponym; toponym; ethnonym; precedent onym